Youth cardiorespiratory fitness: evidence, myths and misconceptions - Armstrong, Neil (Bull World Health Organ, 2019)
Rigorously determined peak oxygen uptake is internationally recognized as the criterion measure of youth cardiorespiratory fitness. The assessment and interpretation of children’s and adolescents’ peak oxygen uptake and the relationship of the measure with other health-related variables are well documented. There has been a recent resurgence of interest in the prediction of peak oxygen uptake from field performance tests in young people. However, coupled with ratio-scaling of data and the raising of clinical red flags, these practices risk clouding our understanding of youth cardiorespiratory fitness and its relationship with current and future health. We believe these methods have the potential to mislead clinical practice and misguide recommendations for the promotion of youth cardiovascular health. We discuss relevant scientific evidence and interpretations that have emerged from predicting youth cardiorespiratory fitness from performance test scores. We argue that children deserve to have health care founded on evidence-based science and not on myths and misconceptions.